6x+5=9x-19

Simple and best practice solution for 6x+5=9x-19 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+5=9x-19 equation:


Simplifying
6x + 5 = 9x + -19

Reorder the terms:
5 + 6x = 9x + -19

Reorder the terms:
5 + 6x = -19 + 9x

Solving
5 + 6x = -19 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
5 + 6x + -9x = -19 + 9x + -9x

Combine like terms: 6x + -9x = -3x
5 + -3x = -19 + 9x + -9x

Combine like terms: 9x + -9x = 0
5 + -3x = -19 + 0
5 + -3x = -19

Add '-5' to each side of the equation.
5 + -5 + -3x = -19 + -5

Combine like terms: 5 + -5 = 0
0 + -3x = -19 + -5
-3x = -19 + -5

Combine like terms: -19 + -5 = -24
-3x = -24

Divide each side by '-3'.
x = 8

Simplifying
x = 8

See similar equations:

| 64-7x=2x+17 | | 2x+3x+1=12-6 | | 6x+14=-40 | | 8-9[9-(3y-7)]= | | 6-9x=29-16x | | 61-7x=11x+23 | | 13-8x=39-22x | | 6-9x=29-6x | | x/2+1=5 | | 2(x-3)=-3x+4 | | 75.60=9x | | 21-2(3+5)= | | x=2(3s-8)+7 | | 4+10x=76+x | | 2x-3(2x-3)=2(3+2x)-13 | | 13x^2=4x-17 | | 7y+7=28 | | 3x+2y-1=8 | | 68-4=7x+24 | | -2y+6x=10 | | 7-4x=-5 | | 6x^2-3x-7=0 | | 12.5=x^2 | | 3t^2+5t-9=0 | | x^3-37x+6=0 | | 23t+5(1-5t)= | | 3t(3t)+5t-9=0 | | 2.5=8x | | -5(a+6)= | | 4069.44=3.14r^2 | | ab+4a+2b+8=0 | | 6(x)-(-10)=38 |

Equations solver categories